Insight into Salivary Gland Proteomes of Two Polyphagous Stink Bugs: Nezara viridula L. and Halyomorpha halys Stål. Issue 7 (8th March 2019) - Serteyn, Laurent; Francis, Frederic
Abstract: The invasive brown marmorated stink bug (BMSB), Halyomorpha halys Stål, and the southern green stink bugs (SGSBs), Nezara viridula L., are widely distributed in Europe, even if the date of introduction and the diet differ. Saliva of Hemipteran pests plays essential roles in the interaction between insects and their host plants. The salivary proteomes of several aphid species have been studied and found to differ according to the species, while no comparative investigation between phytophagous stink bugs has been performed yet. Here, the salivary proteins from two bugs, BMSB and SGSB, are analyzed using LC‐MS/MS. Data are available via ProteomeXchange with identifiers PXD011920 and PXD011976. A total of 238 and 305 proteins are identified in salivary glands of BMSB and SGSB, respectively. In comparison with salivary proteome from other Hemiptera, the most striking feature of the salivary gland proteomes of SGSB and BMSB is the similar pattern of protein functions between both species. Some of the proteins are speculated to play a significant role in plant–insect interactions. The results herein provide a framework for future research to elucidate the molecular basis of differential impact of piercing–sucking insects on host plants.